Muhlenbergia capillaris Muhly Grass: FPS415/FP415, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of Muhlenbergia capillaris, commonly known as muhly grass. It describes the plant’s physical characteristics, including its height, spread, and growth habit. The document highlights the plant’s adaptability to various soil types and environmental conditions, such as drought and flooding. It also outlines the plant’s uses in landscaping, emphasizing its ornamental features and low maintenance requirements. Additionally, the document notes that muhly grass is native to Florida and is not known to be invasive. Original publication date September 1999.